2013
DOI: 10.1007/s11284-013-1084-3
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatic signals deduced from riparian versus upland forest interior pines in North Karelia, Finland

Abstract: Radial growth of boreal tree species is only rarely studied in riparian habitats. Here we investigated chronologies of earlywood, latewood, and annual ring widths and blue intensity (BI; a surrogate to latewood density) from riparian lake shore and upland forest interior pines (Pinus sylvestris L.) growing in boreal forest in eastern Finland. Riparian and upland chronologies were compared to examine differences in the pine growth variability and growth response to climatic variation in the two habitats. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The sensitivity of the lake-shore pines to precipitation, in addition to the positive summer temperature association, is likely linked to lake-level variability. Similar results were obtained by Helama et al (2013), comparing lake-shore and upland trees in Finland. However, in addition to positive associations with summer temperature, they found a strong negative impact of winter precipitation on lake-shore trees.…”
Section: Tree-rings and Climate-present Daysupporting
confidence: 86%
See 2 more Smart Citations
“…The sensitivity of the lake-shore pines to precipitation, in addition to the positive summer temperature association, is likely linked to lake-level variability. Similar results were obtained by Helama et al (2013), comparing lake-shore and upland trees in Finland. However, in addition to positive associations with summer temperature, they found a strong negative impact of winter precipitation on lake-shore trees.…”
Section: Tree-rings and Climate-present Daysupporting
confidence: 86%
“…Discrepancies between pines from respective environments have been noted in studies based on living trees (Düthorn et al, 2013;Helama et al, 2013). Although no attempts have been made to assess this relationship further back in time, our unique treeline data, covering parts of the last millennium, made it possible to assess the nature of this relationship back in time.…”
Section: Implications Of the Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Likely this is due to the local growth environment, where periodical shifts in lake levels may cause varying responses to temperature in the trees, as has been suggested for TRW (e.g. Düthorn et al 2013;Helama et al 2013, Linderholm et al 2014b). In addition to humidity, other factors such as forest composition, exposure to wind and light, aspect, terrain, etc., can also influence the microclimate.…”
Section: Discussionmentioning
confidence: 84%
“…in the eastern Iberian peninsula is function of differences in elevation and distance from the riverbank. Helama et al (2013) examined the dendroclimatic signals of riparian and upland pines forest interior in Finland, and showed that the former reacted negatively to increased rainfall in June, whereas the latter showed a positive response to the same climatic forcing. Dudek et al (1998) founded that differences in elevation modulate the response of Populus deltoids W. Bartram ex Humphry Marshall and Juglans nigra L. to streamflow and climate.…”
Section: Discussionmentioning
confidence: 99%